Estrogen receptor 1 gene polymorphisms and decreased risk of obesity in women - Goulart, Alessandra C.; Zee, Robert Y.L.; Rexrode, Kathryn M. (Metabolism, clinical and experimental, 2009)
Estrogen receptor α gene ( ESR1) polymorphisms have been associated with several diseases, but whether they are associated with obesity is uncertain. To elucidate the role of genetic variation in the ESR1 gene with body mass index (BMI), 543 white women (median age, 63 years) from the Women's Health Study were examined. Most were postmenopausal (99.3%). The relationships between rs2234693 and rs9340799 genotypes and their associated haplotypes with obesity (BMI ≥30 kg/m 2) and overweight (BMI ≥25 kg/m 2) were evaluated. Among women with the rs2234693 TT genotype, 18.3% were obese, whereas only 8.2% of those with the CC genotype were obese ( P = .04). In a logistic regression model assuming additive inheritance, rs2234693 was associated with decreased odds of obesity (BMI ≥30 kg/m 2) (crude odds ratio = 0.63, 95% confidence interval = 0.44-0.90, P = .01). For rs9340799, only an inverse trend was observed for BMI ( P = .08). Haplotypes that included the variant C allele were associated with a reduced risk of obesity (crude odds ratio = 0.65, 95% confidence interval = 0.44-0.94, P = .02 for C-G). The rs2234693 C allele of ESR1 and its associated genotypes and haplotypes were inversely and consistently associated with obesity. One or more copies of the C allele were associated with decreased risk of obesity in white postmenopausal women.